Bilateral versus ipsilesional cortico-subcortical activity patterns in stroke show hemispheric dependence - Vidal, A. Cristina (2017)
Background Understanding of interhemispheric interactions in stroke patients during motor control is an important clinical neuroscience quest that may provide important clues for neurorehabilitation. In stroke patients, bilateral overactivation in both hemispheres has been interpreted as a poor prognostic indicator of functional recovery. In contrast, ipsilesional patterns have been linked with better motor outcomes. Aim We investigated the pathophysiology of hemispheric interactions during limb movement without and with contralateral restraint, to mimic the effects of constraint-induced movement therapy. We used neuroimaging to probe brain activity with such a movement-dependent interhemispheric modulation paradigm. Methods We used an fMRI block design during which the plegic/paretic upper limb was recruited/mobilized to perform unilateral arm elevation, as a function of presence versus absence of contralateral limb restriction ( n = 20, with balanced left/right lesion sites). Results Analysis of 10 right-hemispheric stroke participants yielded bilateral sensorimotor cortex activation in all movement phases in contrast with the unilateral dominance seen in the 10 left-hemispheric stroke participants. Superimposition of contralateral restriction led to a prominent shift from activation to deactivation response patterns, in particular in cortical and basal ganglia motor areas in right-hemispheric stroke. Left-hemispheric stroke was in general characterized by reduced activation patterns, even in the absence of restriction, which induced additional cortical silencing. Conclusion The observed hemispheric-dependent activation/deactivation shifts are novel and these pathophysiological observations suggest short-term neuroplasticity that may be useful for hemisphere-tailored neurorehabilitation.